Evaluasi Tingkat Kualitas Pencahayaan Pada Gedung Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Purwokerto - Muhammad Yusuf Yusuf; Winarso Winarso (Jurnal Riset Rekayasa Elektro, 2022)
Good lighting intensity can affect the quality of performance in activity, improper lighting can also cause mental stress on room users, eye disorders, and disorders of the body. This research was created to analyze the needs and suitability of light quality by performing calculations of lamp types, luxmeter measurements and visualization using Dialux. Dialux is software for simulating, visualizing, and analyzing the performance of lighting systems in geographic locations and environments of specific objects, with optimal lighting situation results. When researching the intensity of lighting in the room in the Building of the Faculty of Teacher Training and Education, one of them in the development laboratory room obtained the results of calculations of 86.66 lux, measurement of luxmeter 83.44 lux, and the results of 109 lux dialux analysis, this is due to shrinkage in the installed lamp, as well as the lack of armature, and lamp point so that the intensity of lighting has not met the Indonesian National Standard of laboratory space of 500 lux. So the solution was made a design recommendation that refers to the Indonesian National Standard. One of the design recommendations made in the development laboratory room obtained results of 561 lux using a type of Meval LED Tube lamp 22 Watts. Because the index in each room is different, when determining the light point must be rounded according to the needs of the room. Keywords :Dialux Visualization, Evaluation of lighting levels, Design recommendations, Indonesian National Standard